PENGARUH PENDIDIKAN, FOREIGN DIRECT INVESTMENT DAN TINGKAT PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI PROVINSI SELURUH INDONESIA - Jaya, I Gede Nova Satria; Widanta, A.A Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023DO - 10.24843/EEB.2023.v12.i11.p10, 2023)
Poverty is one of the macroeconomic variables in a country which has always been a problem in developing countries, especially Indonesia. Poverty is the main factor in the emergence of problems such as crime, inequality, unemployment (another consequence of low levels of education) and other problems. Many factors cause poverty, one of which is a basic need which is education. The research objectives to be achieved are to analyze the simultaneous effect of education, unemployment rate, and Foreign Direct Investment on Poverty in Provinces throughout Indonesia and to analyze the partial effect of education, unemployment rate, and Foreign Direct Investment on Poverty in Provinces throughout Indonesia. The analysis technique uses multiple linear regression analysis. The results of the study are that education partially has a negative and significant effect on the level of poverty in Indonesia, where the longer the average formal education a person has completed, the lower the poverty rate in Indonesia. Foreign Direct Investment partially has a negative but not significant effect, meaning that Foreign Direct Investment has no effect on the Poverty Level. The Unemployment Rate partially has a positive but not significant effect, meaning that the Unemployment Rate has no effect on the Poverty Level.